Texts and artefacts: collected essays on early Christian manuscripts - Hurtado, Larry W. (Library of New Testament studies, 2018)
"Cover" -- "Half Title" -- "Title" -- "Copyright Page" -- "Dedication " -- "Contents" -- "Reprint Permissions" -- "Preface" -- "Abbreviations" -- "Introduction" -- "Text-Critical and Text-Historical Studies" -- "Manuscripts as Artefacts" -- "Summarizing Remarks" -- "Part I Text-Critical and Text-Historical Studies" -- "Chapter 1 The New Testament in the Second Century: Text, Collections and Canon*" -- "Textual Transmission of the New Testament Writings" -- "Newly Published Manuscripts" -- "Second-Century Citations" -- "Collections" -- "Canon" -- "Conclusion" -- "Chapter 2 The Early New Testament Papyri: A Survey of Their Significance" -- "The Manuscripts" -- "Principal New Testament Papyri" -- "The Other Earliest Witnesses" -- "Amount of New Testament Text" -- "Provenance" -- "Text-Critical Significance" -- "Conclusion" -- "Chapter 3 New Testament Scholarship and the Dating of New Testament Papyri *" -- "The Importance of Papyri Dates for Scholarsin New Testament/Christian Origins" -- "New Testament Scholars and Dating Manuscripts" -- "Conclusion" -- "Chapter 4 God or Jesus? Textual Ambiguity and Textual Variantsin Acts of the Apostles" -- "The Data" -- "Analysis" -- "Conclusion" -- "Part II Manuscripts as Artefacts" -- "Chapter 5 The âMeta-Dataâ of Earliest Christian Manuscripts *" -- "The Codex Format" -- "Nomina Sacra" -- "The âStaurogramâ" -- "Other Features of Christian Manuscripts" -- "Conclusion" -- "Chapter 6 Manuscripts and the Sociology of Early Christian Reading" -- "I" -- "II" -- "The Social Setting of Early Christian Reading" -- "Early Christian Manuscripts" -- "Conclusion" -- "Chapter 7 The Origin of the Nomina Sacra: A Proposal*" -- "I" -- "II" -- "III" -- "IV" -- "Chapter 8 The Staurogramin Early Christian Manuscripts: The Earliest Visual Referenceto the Crucified Jesus?" -- "Early Christian Monograms".